A TECHNIQUE FOR INTRODUCTION OF THE PROJECT APPROACH IN TO THE CURRENT CRISIS MANAGEMENT SYSTEM OF THE INDUSTRIAL ENTERPRISE - A. A. Vorobyev (Real Economics Publishing House, 2014)
The use of project-based approach to crisis management requires the formation of a special methodology for its implementation. To solve this problem is a schematic diagram of this process, reflecting its basic methodological principles identified by the author. The features of the implementation of the project approach to crisis management are covered. The algorithm for its implementation, reflecting the peculiarities of management activities in a crisis is proposed.